2011
DOI: 10.1073/pnas.1019034108
|View full text |Cite|
|
Sign up to set email alerts
|

Bioluminescence imaging of Aβ deposition in bigenic mouse models of Alzheimer's disease

Abstract: The undersigned authors wish to note, "The KefFC system of E. coli is maintained in an inactive state by the binding of glutathione (GSH) and is activated by the formation of GSH adducts (GSX), particularly those with bulky substituents. We described two crystal structures with density present in the ligand-binding domain that we interpreted as GSH and GSX. Recently, an independent, experienced crystallographer, who had viewed the structures from our study in a different context, made representations to us tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 39 publications
2
109
0
1
Order By: Relevance
“…Previously, we demonstrated that neurodegeneration can be monitored in living mice by performing bioluminescence imaging (BLI) on the brains of Tg(Gfap-luc) mice (29,30). In these mice, neurodegeneration triggers reactive astrocytic gliosis, resulting in a concomitant increase in Gfap transcription, which can be quantified using BLI.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that neurodegeneration can be monitored in living mice by performing bioluminescence imaging (BLI) on the brains of Tg(Gfap-luc) mice (29,30). In these mice, neurodegeneration triggers reactive astrocytic gliosis, resulting in a concomitant increase in Gfap transcription, which can be quantified using BLI.…”
Section: Resultsmentioning
confidence: 99%
“…BLI has proved useful in monitoring neurodegeneration in various Tg mouse models (Keller et al, 2009;Tamgüney et al, 2009;Watts et al, 2011). Here we demonstrate that it can be used to predict drug efficacy before extension in survival is evident.…”
Section: Discussionmentioning
confidence: 99%
“…This obstacle has been overcome by performing BLI of A␤ plaque-associated astrocytic gliosis. Bigenic mice expressing both mutant human APP and a luciferase reporter driven by the Gfap promoter exhibit an age-dependent increase in the brain BLI signal, which can be accelerated by intracerebral inoculation with A␤ aggregatecontaining samples (72,73). Induction of Tau deposition by intracerebral injection of brain homogenate from either aged Tg mice expressing mutant human Tau or patients with various tauopathies has been observed in Tg mice expressing WT human Tau, which do not spontaneously develop Tau aggregates in their brains (74,75).…”
Section: Mouse Models For Studying the Expanding Universe Of Prion DImentioning
confidence: 99%